Analysis Of Service Quality, Facilities And Price Towards Loyalty With Student Satisfaction As An Intervening Variable At Universitas Pembangunan Panca Budi - Elisya Azmelia; Nurfafrina Siregar; Mesra B (International Journal of Society and Law, 2024)
This research aims to analyze service quality, facilities and prices on loyalty with student satisfaction as intervening variable at the Panca Budi Development University. This type of research is associative with a quantitative approach. The sampling technique used is probability sampling. The sample size in this study was 176 master's students at the Panca Budi Development University. The data analysis method used in this research is the Structural Equation Model (SEM) with SmartPLS v4.0 data processing. The Adjusted R-square results on the loyalty variable have a value of 0.512, which means that this loyalty variable is influenced by service quality, facilities, price and satisfaction by 51.2%, and the Adjusted R-square results on the satisfaction variable have a value of 0.585, which means the satisfaction variable influenced by service quality, facilities and price is only 58.5%. The results of this research show that: (1)There is an influence of service quality on satisfaction with a p-value (0.003) (2)There is an influence of facilities on satisfaction with a p-value (0.001). (3)There is an influence of price on satisfaction with a p-value (0.000). (4)There is an influence of service quality on loyalty with a p-value (0.001). (5)There is an influence of facilities on loyalty with a p-value (0.001). (6)There is an influence of price on loyalty with a p-value (0.000). (7)There is an influence of satisfaction on loyalty with a value of p-(0.001) (8)There is an influence of service quality mediated by satisfaction on loyalty with a value of p-(0.005). (9)There is an influence of facilities mediated by satisfaction on loyalty with a p-value (0.001). (10)There is an influence of price mediated by satisfaction on loyalty with a p-value (0.005).